O programa reuni como vetor de economicidade nas IFES: estudo de caso no setor de transporte da Prefeitura Universitária da UFPB - Gomes , Mauro Pontes e (2017)
The federal government has adopted & series of measures to return the growth of public higher education, creating conditions to promote the physical, academic and pedagogical expansion of the federal higher education. This program has presented the possibility of making a proposal for restructuring and expansion to the period 2008-2012. Among the many allocations of REUNI's resources in the UFPB, the university city hall has become one of them. The present study has as & working platform of the application and management for the resources of REUNI regarding the reduction of costs in the Transport Sector of the PU / UFPB, whose main objective of its development was to analyze if the resources coming from the REUNI PROGRAM, applied in the renewal of the fleet of vehicles of the transport sector of the UFPB, resulted in the decrease of expenses with fuels and maintenance. In its methodology, the case study and the exploratory research were used, and the data treatment was done from the quantitative analysis using Excel. It was concluded, therefore, that the REUNI Program was instrumental in improving the activities carried out by the Transport Sector of the UFPB, contributing to a reduction of operational costs of the fleet, mainly in improving the quality of the services provided.